Self-Management Strategies and Mastery Learning's Impacts on Civic Education Among Senior Secondary School Students - Lasisi, Adekola Kamil; Ibraheem, Islamiyyah Olajire; Muibudeen, Ismail Alabi (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
This study examined self-management strategies and mastery learning's impacts on learning outcomes in civic education among senior secondary school students in Ilorin metropolis. The study employed a pretest, post-test and control group quasi-experimental design using a 3 x 2 x 3 factorial matrix. The population of this study comprised all the SS2 students in public senior secondary schools in Ilorin South. Stratified random sampling techniques were used to select the 75 SS2 students for the study. Data collected was analysed using t-test and analysis of variance (ANOVA). The result of the findings revealed that both self-management strategies and mastery learning significantly contribute to improved learning outcomes in civic education. Students who engaged in self-directed learning and mastery-oriented approaches demonstrated enhanced understanding and mastery of civic education concepts. It was recommended that there is a need to raise student awareness about the benefits of self-management and mastery learning. Encouraging students to take ownership of their learning, set goals, and adopt strategies that align with their learning styles.